Penggunaan Media Nearpod untuk Meningkatkan Minat Siswa terhadap Literasi Matematis di MTs Madrasatul Qur’an Salafiyah (International Forum of Researchers and Lecturers, 2025)
Based on observations made at MTs Madrasatul Qur'an Salafiyah in class VII, student interest in mathematical literacy is low, with a percentage of student interest reaching only 45%. This is due to the implementation of learning that is limited to textbooks and situations in the classroom, which makes students quickly feel bored when reading because the material read is dominated by text. This study aims to determine and explain the effect of using Nearpod media in increasing student interest in mathematical literacy at MTs Madrasatul Qur'an Salafiyah. The population studied included all VII class students totaling 74 people, with the sampling technique using saturated sampling. This research is classified as classroom action research (PTK) with data collection techniques through observation, questionnaires, interviews, and documentation. The instruments used in this study consisted of questionnaires and observation sheets. The data obtained from the research were then analyzed with a quantitative descriptive approach. The results showed an increase in interest in mathematical literacy through the use of poster media identified in cycle I and cycle II. In cycle I, students' interest in mathematical literacy reached 65%, while in cycle II it increased to 90%. This shows that the use of Nearpod media successfully increased students' interest in mathematical literacy.